IMPLEMENTASI FUNGSI PERATURAN WALIKOTA NO.79 TAHUN 2010 TENTANG PEMBATASAN USAHA WARALABA MINIMARKET DI KOTA YOGYAKARTA (STUDI KEBERADAAN USAHA INDOMART DAN ALFAMART DI DAERAH ISTIMEWA YOGYAKARTA) - Ulfa Roffilah Meiyona; Hilyatul Asfia; Qisthi Karami (JOURNAL EQUITABLE, 2021)
This study aims to determine the implementation of Perwal No. 79 of 2010 on the existence of networked Indomaret and Alfamart businesses in Yogyakarta and the attitude of the government and to find an ideal design or form of arrangement related to the existence of the networked Indomaret and Alfamart franchise businesses. This research is a type of normative-empirical law research regarding the implementation of normative legal provisions in their actions in every legal event. The results of this study are based on the urgency of the problem based on several factors related to the law enforcement process in Perwal No. 79 of 2010 on the existence of networked Indomaret and Alfamart businesses in Yogyakarta. The conclusion of this study is that the implementation of the Yogyakarta Mayor's Regulation Number 79 of 2010 concerning the limitation of minimarket franchise businesses in the city of Yogyakarta has not gone well, the existing rules for the franchise business itself are based on the rules as many as 52 units, while in practice there are more than 52 franchise units.